The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1029/2009gl040541
|View full text |Cite
|
Sign up to set email alerts
|

How different would tropospheric oxidation be over an ice‐free Arctic?

Abstract: [1] Climate projections suggest that a complete Arctic seaice retreat is likely in the future during summer. Less ice will cause less light reflection and slower tropospheric photolysis. We use a tropospheric chemistry model to examine how oxidation may differ over an ice-free Arctic. We find that late-summer OH concentrations can decrease by 30 -60% at polar latitudes, while effects on local ozone and global oxidant abundances are small. Ozone changes become larger in the more extreme case where sea-ice is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…A recent calculation demonstrates that the sea salt produced in association with blowing snow events could be a significant bromine source (Yang et al, 2008), which is consistent with recent insitu measurements of higher bromide levels in blowing snow in coastal Antarctica (Jones et al, 2009). Inclusion of this source in the Arctic has a significant effect on tropospheric BrO and oxidation (through ozone and OH) (Voulgarakis et al, 2009).…”
Section: Introductionsupporting
confidence: 67%
“…A recent calculation demonstrates that the sea salt produced in association with blowing snow events could be a significant bromine source (Yang et al, 2008), which is consistent with recent insitu measurements of higher bromide levels in blowing snow in coastal Antarctica (Jones et al, 2009). Inclusion of this source in the Arctic has a significant effect on tropospheric BrO and oxidation (through ozone and OH) (Voulgarakis et al, 2009).…”
Section: Introductionsupporting
confidence: 67%
“…Ozone recovery in the three simulations assuming reduced halogen (ORLM, ORHM, ORCC) does indeed result in generally decreased rates of photolysis of ozone in the O 3 + hv → O( 1 D) channel by roughly 1% in summer, but those changes are mostly insignificant for the 10 year runs considered here (Figure ). Significant decreases of approximately 10% occur in the near‐surface O 3 → O( 1 D) photolysis rate during summer over sea in the Arctic and Antarctic (in the CC and ORCC simulations); these are due to a reduction of sea ice cover in these runs under climate change (of about 2/3 in August), which causes the surface albedo to decrease [ Voulgarakis et al ., ]. Note that in the model, sea ice albedo is in the range of 0.57–0.8, depending on snow cover.…”
Section: Sensitivity To Climate Change Ozone Recovery and Increasinmentioning
confidence: 99%
“…A reduction in Arctic sea ice would reduce the importance of this process in the chemistry of the Arctic atmosphere. In chemistry model simulations, Voulgarakis et al (2009) found large spring ozone increases (up to 50-60%) over the Arctic, due mainly to a reduction in the impact of bromine chemistry, caused by sea-ice retreat. Tropospheric ozone has a relatively small radiative impact (warming), although the effect is greater over bright surfaces (Shindell et al 2006).…”
Section: Ozone and Bromine (Marine)mentioning
confidence: 99%